1991
DOI: 10.1021/bi00245a006
|View full text |Cite
|
Sign up to set email alerts
|

Self-association of human and porcine relaxin as assessed by analytical ultracentrifugation and circular dichroism

Abstract: The self-association properties of recombinant DNA derived human relaxin, and porcine relaxin isolated from porcine ovaries, have been studied by sedimentation equilibrium analytical ultracentrifugation and circular dichroism (CD). The human relaxin ultracentrifuge data were adequately defined by a monomer-dimer self-association model with an association constant of approximately 6 x 10(5) M-1, whereas porcine relaxin was essentially monomeric in solution. An approximate 5-fold increase in weight fraction of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 32 publications
1
39
0
Order By: Relevance
“…The remaining absorption profiles were considered as the best estimate for the residual blank absorption and were subtracted from the sample absorption profiles to obtain the c r values as a function of r. The standard equilibrium equation for a monomer has been used by the Beckman software. This software is based on nonlinear least squares techniques (17) and the Equilibrium/ Velocity Analysis Programs of Holladay and co-workers (18,19).…”
Section: Methodsmentioning
confidence: 99%
“…The remaining absorption profiles were considered as the best estimate for the residual blank absorption and were subtracted from the sample absorption profiles to obtain the c r values as a function of r. The standard equilibrium equation for a monomer has been used by the Beckman software. This software is based on nonlinear least squares techniques (17) and the Equilibrium/ Velocity Analysis Programs of Holladay and co-workers (18,19).…”
Section: Methodsmentioning
confidence: 99%
“…Materials-Recombinant human relaxin, in both the native (B29) and the extended (B33) forms, was synthesized at Genentech, Inc. (18). 1 The B33 form contained a 4-amino acid extension (Lys-Arg-Ser-Leu) at the carboxyl terminus of its B-chain (19) and was used for 32 P labeling.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis by circular dichroism before and after dilution resulted in an approximate 5-fold increase in monomer, indicating that there was no difference in the far UV CD spectrum, whereas there were significant decreases in the intensity of the tyrosine CD band near 277 nm and the tyrosine and tryptophan CD band at 284 nm. Moreover, there was little change in the broad band at 295 nm due solely to tryptophan suggesting that the environment of the lone tyrosine rather than the two tryptophans changed upon dilution (Shire et al 1991) (Fig. 1).…”
Section: Self-association Of Small Non-glycosylated Proteinsmentioning
confidence: 98%
“…Early characterization of human relaxin by size exclusion chromatography (SEC-HPLC) suggested that the molecule exists in the monomeric form (data not shown). However, studies using sedimentation equilibrium analytical ultracentrifugation (SE-AUC) and circular dichroism (CD) clearly showed that this molecule undergoes concentration dependent self-association, which was not detected by SEC because of the dilution that occurs during the chromatography (Shire et al 1991). Analysis by circular dichroism before and after dilution resulted in an approximate 5-fold increase in monomer, indicating that there was no difference in the far UV CD spectrum, whereas there were significant decreases in the intensity of the tyrosine CD band near 277 nm and the tyrosine and tryptophan CD band at 284 nm.…”
Section: Self-association Of Small Non-glycosylated Proteinsmentioning
confidence: 99%
See 1 more Smart Citation